D. I. BLOKHINTSEV – SCIENTIST AND TEACHER. THE SPIRITUAL FOUNDATIONS OF SCIENTIFIC WORK - V. N. Pervushin (Образование и наука)
The aim of the publication is to state the creative principles of activity of the outstanding scientist and teacher Dmitry Ivanovich Blokhintsev (1/10/1908 – 1/29/1979) – the organizer and the first director of the Joint Institute for Nuclear Researches in Dubna in 1956–1965, one of the pioneers of Nuclear Science and Atomics, the corresponding member of the Academy of Sciences of the USSR.The author of the article shares memories about the teacher and the research supervisor, and gives a peculiar report on realization of ideas of D. I. Blokhintsev. D. I. Blokhintsev had the special, original point of view on spiritual bases of scientific creativity that was directly reflected in his research and pedagogical activity.There are two fundamental aspects of pedagogics. On the one hand, it is the science possessing own specific laws and methods. On the other hand, the pedagogics is an art which methods, unlike scientific methodologies, can’t be acquired by formal and logical schemes. They are broadcast from one personality to another in direct communication. Thus possibly the «correspondence» assimilation of methods of outstanding teachers is inefficient as a rule. Not enough attention in the press is paid to this informal aspect of pedagogics in the view of difficulty of its description and analysis. The discussed D. I. Blokhintsev’s heritage is valuable from positions of the characteristic of pedagogics as arts of creative skill transfer. At first sight, it can seem paradoxical that this part of pedagogics is considered in connection with work in the field of the Quantum Field Theory and Cosmology – one of the most formalized fields of Theoretical Physics. However, the science, as well as pedagogics, considering it from top-level creativity, is becoming some kind of art too.One more important direction of work of D. I. Blokhintsev continued by the author of the publication in the book «Principles of the Quantum Universe» is emphasized. It is connected with the development of idea about vacuum as a source of all variety of the material world surrounding us. This deep world outlook idea includes both philosophical and religious aspects. D. I. Blokhintsev was presented the Order of Saints of Cyril and Methodius of the 1st degree (Bulgaria, 1970) for his fundamental course «Bases of Quantum Mechanics» published in nine languages. The scientist was the chairman of the organizing committees of 17 international conferences «Science, Philosophy and Religion» held in Dubna from 1990 to 2015 together with Institute of Philosophy of the Russian Academy of Sciences, the Moscow Spiritual Academy in Sergiev Posad, Fund of Andrew the FirstCalled, and Center of National Glory of Russia.D. I. Blokhintsev not only has enriched world science with fundamental works in the field of Solid State Physics and Statistical Physics, Acoustics, Physics Of Reactors And Nuclear Power, Quantum Mechanics, Quantum Field Theory and Quantum Electrodynamics, Physics Of High Energy and an Atomic Nucleus, Philosophy and Methodology of Science, but also left the reserve stimulating creative scientific activity for future generation. The article shows how the principles of scientific creativity of D. I. Blokhintsev work in Modern Physics and Cosmology of the Universe.